Contribution of Snacks and Physical Activities to Elevated Blood Pressure of Adolescent Girls in West Java, Indonesia - Rahfiludin, Mohammad Zen; Asna, Alfi Fairuz; Suroto; Hidayanti, Lilik (Malaysian Journal of Medicine and Health Sciences, 2023)
Introduction: The prevalence of hypertension in Indonesia has continued to increase over the last few years. An unhealthy diet and lack of physical activity can elevate blood pressure, particularly if an unhealthy lifestyle has been followed since adolescence. This study aimed to analyze the correlation between snack consumption and physical activity with blood pressure in adolescent girls. Methods: A cross-sectional study was conducted with 349 adolescent girls from seven Islamic boarding schools in West Java, Indonesia. Data on daily food and snack consumption were obtained by the 24-hour recall for 3 non-consecutive days. Blood pressure was measured using a digital blood pressure instrument, and the results were categorized by age, gender, and height. Linear regression analyses were performed to investigate determinants of blood pressure. Results: A total of 120 (34.4%) of the adolescent girls in the study had hypertension. A majority of girls had inadequate daily intake (energy, fat, carbohydrates, and sodium; only total protein intake met Indonesia’s recommended dietary allowance). Snacks were found to be high in protein, fat, and carbohydrates, with consumption levels above 15%. More than half (61.9%) of the subjects’ daily sodium intake came from snacks. Low-fat intake from snacks was associated with an increase in blood pressure in this study. Daily nutritional intake affecting blood pressure included sodium and total fat intake. Lack of physical activity in adolescent girls was not a risk factor for elevated blood pressure. Conclusion: Fat and sodium intake was associated with elevated blood pressure in adolescent girls. REFERENCES WHO. Global Non-Communicable Disease Target: Reduce High Blood Pressure. World Health Organization. 2016;:190-215.[Google Scholar] National Institute of Health Research and Development. National Report on Basic Health Research 2013. National Institute of Health Research and Development Ministry of Health Republic of Indonesia; 2013. National Institute of Health Research and Development. National Report on Basic Health Research 2018. Jakarta, Indonesia: National Institute of Health Research and Development Publishing Office; 2019. Urbina E, Lande M, Hooper S, Daniels S. Target Organ Abnormalities in Pediatric Hypertension. The Journal of Pediatrics. 2018. November;202:14-22. https://doi.org/10.1016/j.jpeds.2018.07.026[Google Scholar][Pubmed][Crossref] Raitakari O, Juonala M, Kähönen M, Taittonen L, Laitinen T, Mäki-Torkko N, Järvisalo M, Uhari M, Jokinen E, Rönnemaa T, Åkerblom H, Viikari JA. Cardiovascular Risk Factors in Childhood and Carotid Artery Intima-Media Thickness in Adulthood. JAMA. 2003;290:2277. https://doi.org/10.1001/jama.290.17.2277[Google Scholar] [Pubmed][Crossref] Belahsen R. Nutrition transition and food sustainability. Proceedings of the Nutrition Society. 2014;73:385-8. https://doi.org/10.1017/S0029665114000135[Google Scholar] [Pubmed] Galal O. The nutrition transition in Egypt: obesity, undernutrition and the food consumption context. Public Health Nutrition. 2002;5:141-8. https://doi.org/10.1079/PHN2001286[Google Scholar] [Pubmed] Peltzer K, Pengpid S. Leisure Time Physical Inactivity and Sedentary Behaviour and Lifestyle Correlates among Students Aged 13–15 in the Association of Southeast Asian Nations (ASEAN) Member States, 2007–2013. International Journal of Environmental Research and Public Health. 2016;13:217. https://doi.org/10.3390/ijerph13020217[<a href="https://scholar.google.com/scholar_lookup?title=Leisure+Time+Physical+Inactivity+and+Sedentary+Behaviour+and+Lifestyle+Correlates+among+Students+Aged+13%E2%80%9315+in+the+Association+of+Southeast+Asian+Nations+%28ASEAN%29+Member+States%2C+2007%E2%80%932013.+International+Journal+of+Environmental+Research+and+Public+Health.+2016%3B13%3A217.+https%3A%2F%2Fdoi.org%2F10.3390%2Fijerph13020217&btnG=">Google Scholar] [PMC free article] [Pubmed] Wyszyńska J, Podgórska-Bednarz J, Dereń K, Mazur A. The Relationship between Physical Activity and Screen Time with the Risk of Hypertension in Children and Adolescents with Intellectual Disability. BioMed Research International. 2017;2017:1-8. https://doi.org/10.1155/2017/1940602[<a href="https://scholar.google.com/scholar_lookup?title=The+Relationship+between+Physical+Activity+and+Screen+Time+with+the+Risk+of+Hypertension+in+Children+and+Adolescents+with+Intellectual+Disability.+BioMed+Research+International.+2017%3B2017%3A1-&btnG=">Google Scholar] [PMC free article] [Pubmed] Durrani A, Fatima W. Effect of Physical Activity on Blood Pressure Distribution among School Children. Advances in Public Health. 2015;2015:1-4. https://doi.org/10.1155/2015/379314[<a href="https://scholar.google.com/scholar?hl=en&as_sdt=0%2C5&q=Effect+of+Physical+Activity+on+Blood+Pressure+Distribution+among+School+Children.+Advances+in+Public+Health.+2015%3B2015%3A1-4.+https%3A%2F%2Fdoi.org%2F10.1155%2F2015%2F379314++&btnG=">Google Scholar] Martinez-Gomez D, Tucker J, Heelan K, Welk G, Eisenmann J. Associations Between Sedentary Behavior and Blood Pressure in Young Children. Archives of Pediatrics & Adolescent Medicine. 2009;163:724-30. https://doi.org/10.1001/archpediatrics.2009.90[Google Scholar] Majane OI, Vengethasamy L, Du Toit E, Makaula S, Woodiwiss A, Norton G. Dietary-Induced Obesity Hastens the Progression From Concentric Cardiac Hypertrophy to Pump Dysfunction in Spontaneously Hypertensive Rats. Hypertension. 2009;54:1376-83. https://doi.org/10.1161/HYPERTENSIONAHA.108.127514[<a href="https://scholar.google.com/scholar_lookup?title=Dietary-Induced+Obesity+Hastens+the+Progression+From+Concentric+Cardiac+Hypertrophy+to+Pump+Dysfunction+in+Spontaneously+Hypertensive+Rats.+Hypertension.+2009%3B54%3A1376-&btnG=">Google Scholar] Ponzo V, Ganzit G, Soldati L, De Carli L, Fanzola I, Maiandi M, Durazzo M, Bo S. Blood pressure and sodium intake from snacks in adolescents. European Journal of Clinical Nutrition. 2015;69:681-6. https://doi.org/10.1038/ejcn.2015.9[Google Scholar] [Pubmed] Mccrory M, Campbell W. Effects of Eating Frequency, Snacking, and Breakfast Skipping on Energy Regulation: Symposium Overview,. The Journal of Nutrition. 2011;141:144-7. https://doi.org/10.3945/jn.109.114918[Google Scholar] [Pubmed][Crossref] Vet D, Stok E, F, Wit D, J, Ridder D, D. The Habitual Nature of Unhealthy Snacking: How Powerful are Habits in Adolescence? Appetite. Internet. 2015;95:182-7. https://doi.org/10.1016/j.appet.2015.07.010[Google Scholar] [Pubmed][Crossref] Roura E, Milà-Villarroel R, Lucía Pareja S, Adot Caballero A. Assessment of Eating Habits and Physical Activity among Spanish Adolescents. The "Cooking and Active Leisure" TAS Program. PLOS ONE. 2016;11:e0159962. https://doi.org/10.1371/journal.pone.0159962[Google Scholar] [Pubmed] Isfandari S. Young Scholar Prize. Indonesia and the Malay World. 2014;42:127-. Ministry of Health Republic of Indonesia. Indonesian Food Composition Data [Internet]. https://www.panganku.org/en-EN/beranda. 2017;. Murakami K, Livingstone ME. Decreasing the number of small eating occasions (<15 % of total energy intake) regardless of the time of day may be important to improve diet quality but not adiposity: a cross-sectional study in British children and adolescents. British Journal of Nutrition. 2016;115:332-41. https://doi.org/10.1017/S0007114515004420[<a href="https://scholar.google.com/scholar_lookup?title=.+Decreasing+the+number+of+small+eating+occasions+%28%3C15+%25+of+total+energy+intake%29+regardless+of+the+time+of+day+may+be+important+to+improve+diet+quality+but+not+adiposity%3A+a+cross-sectional+study+in+British+children+and+adolescents&btnG=">Google Scholar] [Pubmed] National High Blood Pressure Education Program Working Group on High Blood Pressure in Children and Adolescents. The Fourth Report on the Diagnosis, Evaluation, and Treatment of High Blood Pressure in Children and Adolescents. PEDIATRICS. 2005;114(2 Suppl 4th Report):555-76. Ministry of Health Republic of Indonesia. Regulation of the Minister of Health of the Republic of Indonesia Number 2 in 2020 concerning Child Anthropometry Standards. 2020;. Marlina Y, Huryati E, Soenarto Y. Indeks massa tubuh dan aktivitas fisik dengan tekanan darah pada pelajar SMA. Jurnal Gizi Klinik Indonesia. 2016;12:160.[Google Scholar] Kurnianto A, Kurniadi Sunjaya D, Ruluwedrata Rinawan F, Hilmanto D. Prevalence of Hypertension and Its Associated Factors among Indonesian Adolescents. International Journal of Hypertension. 2020;2020:1-7. https://doi.org/10.1155/2020/4262034[Google Scholar] [Pubmed] Mai TT, Gallegos D, Jones L, Tran Q, Tran TH, Van Der Pols J. The utility of anthropometric indicators to identify cardiovascular risk factors in Vietnamese children. British Journal of Nutrition. 2020;123:1043-55. https://doi.org/10.1017/S0007114520000203[Google Scholar] [Pubmed] Çam H, Ustuner Top F. Prevalence of Hypertension and Its Association with Body Mass Index and Waist Circumference Among Adolescents in Turkey: A Cross-Sectional Study. Journal of Pediatric Nursing. 2021;57:e29-e33. https://doi.org/10.1016/j.pedn.2020.09.017[<a href="https://scholar.google.com/scholar_lookup?title=Prevalence+of+Hypertension+and+Its+Association+with+Body+Mass+Index+and+Waist+Circumference+Among+Adolescents+in+Turkey%3A+A+Cross-Sectional+Study&btnG=">Google Scholar] [Pubmed] Zou Y, Xia N, Zou Y, Chen Z, Wen Y. Smartphone addiction may be associated with adolescent hypertension: a cross-sectional study among junior school students in China. BMC Pediatrics. 2019;19:1-8. https://doi.org/10.1186/s12887-019-1699-9[Google Scholar] [Pubmed] Goel R, Misra A, Agarwal S, Vikram N. Correlates of hypertension among urban Asian Indian adolescents. Archives of Disease in Childhood. 2010;95:992-7. https://doi.org/10.1136/adc.2009.162347[Google Scholar][Pubmed] Ministry of Health Republic of Indonesia. Ministerial Regulation on Health No. 28 of 2019 concerning Recommended Nutritional Adequacy Rate for the Indonesian People. 2019;. Chobanian V, Bakris G, Black H, Cushman W, Green L, Joseph I, L. The Seventh Report of the Joint National Committee on Prevention, Detection, Evaluation, and Treatment of High Blood Pressure<SUBTITLE>The JNC 7 Report</SUBTITLE>. JAMA. 2003 May 21;289:2560. https://doi.org/10.1001/jama.289.19.2560[Google Scholar] [Pubmed][Crossref] Cohen H, Hailpern S, Alderman M. Sodium Intake and Mortality Follow-Up in the Third National Health and Nutrition Examination Survey (NHANES III). Journal of General Internal Medicine. 2008;23:1297-302. https://doi.org/10.1007/s11606-008-0645-6[Google Scholar][Pubmed] He FJ, Marrero NM, MacGregor GA. Salt and blood pressure in children and adolescents. Journal of Human Hypertension. 2007 09 06;22(1):4-11. https://doi.org/10.1038/sj.jhh.1002268[Google Scholar] [Pubmed] Hassana N, El Shebinib S, El-Masrya S, Ahmedb N, Alia M, El-Saeedc GM, El-Lebedyd D. Association between dietary sodium, calcium, saturated fat and blood pressure in obese Egyptian adolescents. Egyptian Pediatric Association Gazette. 2019;67. https://doi.org/10.1186/s43054-019-0007-5[Google Scholar] Hojhabrimanesh A, Akhlaghi M, Rahmani E, Amanat S, Atefi M, Najafi M, Hashemzadeh M, Salehi S, Faghih S. A Western dietary pattern is associated with higher blood pressure in Iranian adolescents. European Journal of Nutrition. 2017;56:399-408. https://doi.org/10.1007/s00394-015-1090-z[Google Scholar] [Pubmed] Ruixing Y, Shangling P, Shuquan L, Dezhai Y, Weixiong L, Qiming F, Yuming C, Yaoheng H, Yijiang Z, Qinchen L. Comparison of hypertension and its risk factors between the Guangxi Bai Ku Yao and Han populations. Blood Pressure. 2008;17:306-16. https://doi.org/10.1080/08037050802589593[Google Scholar] [Pubmed] Schröder H, Schmelz E, Marrugat J. Relationship between diet and blood pressure in a representative Mediterranean population. European Journal of Nutrition. 2002;41:161-7. https://doi.org/10.1007/s00394-002-0372-4.[Google Scholar] [Pubmed] Leyvraz M, Chatelan A, Da Costa B, Taffé P, Paradis G, Bovet P, Bochud M, Chiolero A. Sodium intake and blood pressure in children and adolescents: a systematic review and meta-analysis of experimental and observational studies. International Journal of Epidemiology. 2018;47:1796-810. https://doi.org/10.1093/ije/dyy121[Google Scholar] [Pubmed]\ Rosner B, Cook N, Daniels S, Falkner B. Childhood Blood Pressure Trends and Risk Factors for High Blood Pressure. Hypertension. 2013;62:247-54. https://doi.org/10.1161/HYPERTENSIONAHA.111.00831[Google Scholar] [Pubmed] Lucan S, Karpyn A, Sherman S. Storing Empty Calories and Chronic Disease Risk: Snack-Food Products, Nutritive Content, and Manufacturers in Philadelphia Corner Stores. Journal of Urban Health. 2010;87:394-409. https://doi.org/10.1007/s11524-010-9453-5[Google Scholar] [PMC free article] [Pubmed] Yuan S, Yu H, Liu M, Tang B, Zhang J, Gasevic D, Larsson S, He Q. Fat Intake and Hypertension Among Adults in China: The Modifying Effects of Fruit and Vegetable Intake. American Journal of Preventive Medicine. 2020;58:294-301. https://doi.org/10.1016/j.amepre.2019.09.004[Google Scholar][Pubmed][Crossref] Morenga L Te, Montez J. Health Effects of Saturated and Trans-Fatty Acid Intake in Children and Adolescents: Systematic Review and Meta-Analysis. PLoS One. 2017;12. https://doi.org/journal.pone.0186672.[Google Scholar] [PMC free article] [Pubmed] Kong A, Beresford SA, Alfano C, Foster-Schubert K, Neuhouser M, Johnson D, Duggan C, Wang C, Xiao L, Bain C, Mctiernan A. Associations between Snacking and Weight Loss and Nutrient Intake among Postmenopausal Overweight to Obese Women in a Dietary Weight-Loss Intervention. Journal of the American Dietetic Association. 2011;111:1898-903. https://doi.org/10.1016/j.jada.2011.09.012[<a href="https://scholar.google.com/scholar_lookup?title=Associations+between+Snacking+and+Weight+Loss+and+Nutrient+Intake+among+Postmenopausal+Overweight+to+Obese+Women+in+a+Dietary+Weight-Loss+Intervention&btnG=">Google Scholar][Pubmed][Crossref] Kim S, Park G, Yang J, Chun S, Yoon H, Park M. Eating frequency is inversely associated with blood pressure and hypertension in Korean adults: analysis of the Third Korean National Health and Nutrition Examination Survey. European Journal of Clinical Nutrition. 2014;68:481-9. https://doi.org/10.1038/ejcn.2014.9[<a href="https://scholar.google.com/scholar_lookup?title=Eating+frequency+is+inversely+associated+with+blood+pressure+and+hypertension+in+Korean+adults%3A+analysis+of+the+Third+Korean+National+Health+and+Nutrition+Examination+Survey&btnG=">Google Scholar][Pubmed] Lee S, Cai H, Yang G, Xu W, Zheng W, Li H, Gao Y, Xiang Y, Shu X. Dietary patterns and blood pressure among middle-aged and elderly Chinese men in Shanghai. British Journal of Nutrition. 2010;104:265-75. https://doi.org/10.1017/S0007114510000383[Google Scholar] [PMC free article] [Pubmed] Appel L, Moore T, Obarzanek E, Vollmer W, Svetkey L, Sacks F, Bray G, Vogt T, Cutler J, Windhauser M, Lin P, Karanja N, Simons-Morton D, Mccullough M, Swain J, Steele P, Evans M, Miller E, Harsha D. A Clinical Trial of the Effects of Dietary Patterns on Blood Pressure. New England Journal of Medicine. 1997;336:1117-24. https://doi.org/10.1056/NEJM199704173361601[Google Scholar][Pubmed] WHO. Candau, Marcolino Gomes, (30 May 1911–25 Jan. 1983), Director-General Emeritus, World Health Organization, Geneva, since 1973. WHO Guidelines on Physical Activity and Sedentary Behaviour. 2020;.[Google Scholar] Welk G, Kim Y, Stanfill B, Osthus D, Calabro M, Nusser S, Carriquiry A. Validity of 24-h Physical Activity Recall. Medicine & Science in Sports & Exercise. 2014;46:2014-24. https://doi.org/10.1249/MSS.000000000000031[Google Scholar] [PMC free article] Luo H, Dodd K, Arnold C, Engle-Stone R. A New Statistical Method for Estimating Usual Intakes of Nearly-Daily Consumed Foods and Nutrients Through Use of Only One 24-hour Dietary Recall. The Journal of Nutrition. 2019;149:1667-73. https://doi.org/10.1093/jn/nxz070[<a href="https://scholar.google.com/scholar_lookup?title=A+New+Statistical+Method+for+Estimating+Usual+Intakes+of+Nearly-Daily+Consumed+Foods+and+Nutrients+Through+Use+of+Only+One+24-hour+Dietary+Recall&btnG=">Google Scholar] [PMC free article]